Optimization of source parameters in dynamic network structure objects - Ashrafova, Yegana; Aida-zade, Kamil (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
The optimization of parameters for concentrated sources that influence the operation of a dynamic network structure is the focus of this study. The network structure comprises numerous one-dimensional objects, each governed by a system of ordinary differential equations with nonlocal boundary conditions to describe their states. Sources affect individual points within these subobjects, as well as their connection points. The optimization process aims to determine the optimal locations and power levels of these sources, based on predefined target functionality criteria. We derive the necessary optimality conditions for the concentrated sources' parameters and present the results of numerical experiments using a test problem as an illustrative example.